Sustainability in multinational companies - Mateo Collantes, Miguel Ángel (Observatorio Medioambiental, 2020)
This study aims to analyze the real capacity to implement sustainability in multinational companies. First we analyze the key concepts, and then we present a background check of multinational companies. The central part of the document is intended to analyze the relationship of companies with the environment and sustainability, what steps companies can take to achieve it, the economic and social complications to achieve the objectives and the benefits that companies and the societies get of sustainable practices. Finally, we present the relationship of the companies with the territory and the industrial estates.
Keywords: Multinational; Sustainable development; Economy; Business management; Benefits